Electrochemical Studies of LbL Films With Dawson Type Heteropolyanion Glassy Carbon Electrode Sensor Modified for Methyl Parathion Detection - Ditta, Nafeesa Allah; Yaqub, Mustansara; Nadeem, Sohail; Jamil, Sundas; Hassan, Sadaf Ul; Iqbal, Shahid; Javed, Mohsin; Elkaeed, Eslam B.; Alshammari, Fwzah H.; Alwadai, Norah; Alzhrani, Rami M.; Awwad, Nasser S.; et al. (Frontiers in Materials, 2022)
Rapid methyl parathion detection was measured using a fabricated glassy carbon electrode (GCE) sensor designed using the layer-by-layer (LBL) method. Multilayer assemblies were developed on the glassy carbon electrode by alternating depositions of anions and cations in which a Dawson Type Polyoxometalate β-K6[(P2W18O62·H2O)]·14H2O (∼P2W18 POM) and polyethyleneimine (PEI) stabilized silver nanoparticles (∼PEI-AgNPs) acted as anions and cations, respectively. The redox behavior of P2W18 POM within LBL assembly was carried out via cyclic voltammetry. This LBL assembly was thoroughly characterized by UV-Visible, FT-IR, XRD, AFM, and SEM techniques. The fabricate GCE sensor was investigated for the electrocatalytic activity to detect methyl parathion. The results clearly showed that the fabricated GCE sensor was successfully synthesized. More interestingly, the current response for detecting methyl parathion was found to be less than 1 ppm, proving that this fabricated GCE sensor may exhibit potential applications in the detection of targeted pesticide.